Impactos ambiental e socioeconômico do uso e ocupação dos solos da microbacia Jardim Novo Horizonte, em Ilha Solteira, SP - Militão, Elza da Silva [UNESP] (2013)
The land occupation in Brazil has been characterized by major cause environmental disturbances. Problems such as soil erosion, siltation of rivers, floods, pollution, and water shortages are related to inappropriate land use. Besides their effect on quality of life and sustainability of the agricultural system, these problems represent considerable economic losses to states and municipalities, and also the depreciation of property and the difficulties faced by owners / producers. Proper management of soil and water is essential for the maintenance of environmental quality and life of the population. However, this has not happened in the watershed Jardim Novo Horizonte, Municipality of Single Island, São Paulo. These areas are found many environmental problems, such as low soil fertility, degraded pasture, soil erosion and siltation of waterways. Because of these problems, the work was to verify, in a perspective of environmental and socio-economic systems present, the effects of the current model of exploration and land use of the watershed Novo Horizonte (comparing it with the changes occurring in perspective inter time). To achieve the objectives field surveys were conducted in 44 batches, interviews with families residing locally analyzed and field information. Regarding the occupation of the study area was found: corn, cane sugar for feeding livestock, vegetables and horticulture producers for own consumption, using predominantly pasture. The problems associated with improper management of natural resources were identified: degraded pasture throughout the watershed, lack of maintenance or lack of mechanical conservation practices, extensive erosion in virtually every watershed, erosion furrow, gully erosion, stream siltation and lack of terracing agriculture in most of the lots of the watershed. The countryside in this microbacia in reference is heterogeneous and does not represent the entire ...